2015
DOI: 10.1002/chem.201503033
|View full text |Cite
|
Sign up to set email alerts
|

Quinoidal Oligo(9,10‐anthryl)s with Chain‐Length‐Dependent Ground States: A Balance between Aromatic Stabilization and Steric Strain Release

Abstract: Quinoidal π-conjugated polycyclic hydrocarbons have attracted intensive research interest due to their unique optical/electronic properties and possible magnetic activity, which arises from a thermally excited triplet state. However, there is still lack of fundamental understanding on the factors that determine the electronic ground states. Herein, by using quinoidal oligo(9,10-anthryl)s, it is demonstrated that both aromatic stabilisation and steric strain release play balanced roles in determining the ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…π-Conjugated polycyclic hydrocarbons (CPHs) with an open-shell singlet ground state have recently attracted much attention in the frontier areas of physical organic chemistry, structural organic chemistry, and materials science . Among various studied CPHs, higher order acenes (longer than pentacene) and extended zethrenes (longer than zethrene) are two closely related systems (Figure a), but they behave quite differently and need more detailed examination. Acenes are linearly fused benzene oligomers, and according to Clar’s sextet rule, higher order acenes will be highly reactive as only one aromatic sextet ring (the ring shaded in blue color in Figure a) can be drawn no matter how long the acene molecule is.…”
Section: Introductionmentioning
confidence: 99%
“…π-Conjugated polycyclic hydrocarbons (CPHs) with an open-shell singlet ground state have recently attracted much attention in the frontier areas of physical organic chemistry, structural organic chemistry, and materials science . Among various studied CPHs, higher order acenes (longer than pentacene) and extended zethrenes (longer than zethrene) are two closely related systems (Figure a), but they behave quite differently and need more detailed examination. Acenes are linearly fused benzene oligomers, and according to Clar’s sextet rule, higher order acenes will be highly reactive as only one aromatic sextet ring (the ring shaded in blue color in Figure a) can be drawn no matter how long the acene molecule is.…”
Section: Introductionmentioning
confidence: 99%
“…According to broken symmetry density functional theory (DFT) calculations, any molecule with a nonzero diradical character in the ground state can be classified as a diradicaloid (diradical-like molecule). So far, various relatively stable PH-based open-shell singlet diradicaloids have been synthesized, for example, bisphenalenyls, zethrenes, indenofluorenes, anthenes, and quinoidal rylenes . Fundamental studies on the structure–diradical character–physical property relationships have revealed that both the aromaticity and the steric strain played important roles in determining the ground-state electronic structure and physical property.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, numerous open-shell singlet biradicaloids based on quinoidal π-conjugated molecules have been developed, including but not limited to quinoidal oligothiophenes, , , thienoacenes, ,,,,, and polycyclic hydrocarbons. ,,, These molecules with biradical character have many prospective applications in organic electronics, , photonics, , and spintronics devices. The biradical character index ( y 0 ) and singlet–triplet energy gap (Δ E S–T ) correlate with third-order nonlinear optical (NLO) responses and magnetic properties of open-shell singlet biradicals. ,, However, extended π systems possessing large biradical character are generally unstable, which poses a profound challenge for the development of synthetic routes to access extended quinoidal oligomers. Several synthetic approaches have been developed to access such oligomers.…”
Section: Introductionmentioning
confidence: 99%
“…π-Conjugated quinoidal molecules have emerged as promising materials because of their air stable n-channel electron transport in organic field-effect transistors, near-infrared (NIR) absorption, and nonlinear optical properties. Recent studies have also revealed the existence of open-shell biradical character for a series of donor–acceptor-based π-conjugated quinoidal molecules. Considering the inherent chemical reactivity of open-shell biradicals at ambient atmosphere, such properties are quite unusual . In these molecular systems, the contorted quinoidal forms with closed-shell singlet electronic ground states are strongly stabilized by π-electron delocalization along the oligoene-like inter-ring CC/C–C alternating pattern .…”
Section: Introductionmentioning
confidence: 99%